2012
DOI: 10.1103/physrevb.86.205427
|View full text |Cite
|
Sign up to set email alerts
|

RKKY interactions in graphene: Dependence on disorder and Fermi energy

Abstract: International audienceWe report, how the indirect exchange interaction JRKKY(R) between magnetic moments at a distance R in graphene depends on nonmagmetic disorder strength W and gate voltage. First, a semiclassical method is used to rederive JRKKY in clean graphene, yielding the asymptotic decay 1/R2+α, where α=1 is the power of the pseudogap at the Dirac point. Next, we perform numerical calculations with the Anderson tight-binding model on a honeycomb lattice. We observe that along the armchair direction J… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 26 publications
5
34
0
Order By: Relevance
“…This strong disorder due to randomly distributed hydrogen impurities influences the electronic wavefunctions by causing the tendency to localization and, therefore, may limit the range of interaction. Such a phenomenon is known for example from the studies of indirect RKKY coupling in disordered systems [45], including the case of indirect coupling in graphene [46,47]. The conclusion can be drawn that the disorder causes damping of amplitude of indirect interaction and also shifts the phase [45].…”
Section: The Magnetic Long-range Interactionmentioning
confidence: 97%
“…This strong disorder due to randomly distributed hydrogen impurities influences the electronic wavefunctions by causing the tendency to localization and, therefore, may limit the range of interaction. Such a phenomenon is known for example from the studies of indirect RKKY coupling in disordered systems [45], including the case of indirect coupling in graphene [46,47]. The conclusion can be drawn that the disorder causes damping of amplitude of indirect interaction and also shifts the phase [45].…”
Section: The Magnetic Long-range Interactionmentioning
confidence: 97%
“…In principle, due to the π bonding and availability of itinerant charges, coupling between localized magnetic moments at various defect sites can be achieved through the Ruderman–Kittel–Kasuya–Yoshida (RKKY) interaction . However, earlier studies concluded that such an interaction in graphene is too weak to result in high T C , and can be even suppressed . Yazyev and Helm found from their early study that the coupling between the magnetic moments can be either FM or AFM, depending on whether the defects are located on the same or different hexagonal sublattices of the graphene lattice, respectively .…”
Section: Spin Generationmentioning
confidence: 99%
“…Although the range of our data is very limited due to computational expense, our results are in general agreement with previous analytical and numerical studies of RKKY interaction in graphene. [26][27][28][29][30][31] Hence, the RKKY is the dominant magnetic coupling interaction that induces the ferromagnetic spin-alignment for configurations with half-metallic electronic structures in Fig.1. When the separation is shorter than 0.3 nm, the magnetic coupling cannot be interpreted simply by the RKKY interaction due to the strong direct interaction between the nitrogen atoms.…”
mentioning
confidence: 99%